The Purchase Intention of Environmentally Friendly Milk Bottles: Role of Product Knowledge and Environmental Concern - Zulfa, Vania; Andini, Nur Fauziah; Hamiyati, Hamiyati (Journal of Consumer Sciences, 2023)
Environmental pollution poses a significant global challenge. The use of environmentally friendly milk bottles can minimize the impact of pollution and is a safer choice, especially for infants. This study aimed to analyze the effect of product knowledge and environmental concerns on the purchase intention of environmentally friendly milk bottles. Employing a quantitative approach, the study involved 100 respondents selected through purposive sampling. The findings show the simultaneous impact of product knowledge and environmental concerns on the intention to purchase environmentally friendly milk bottles. This implies that higher consumer knowledge about the product and increased environmental awareness is positively correlated with a greater inclination to buy environmentally friendly milk bottles. The implication of this study underscores the importance of promoting awareness and education regarding the use of environmentally friendly products to enhance consumer intentions toward such products.